Investigating the SDG 4 Framework: The (Non)Influence of Learning Styles on English Achievement in a Rural Islamic Elementary School - Atika Salman; Salah Mohammed Abd Allah Adam; Reza Yavarian; Nabil Bousseliou (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: In simple words tell to readers about the aim of this study. No discussion, no story only aim of this study [30-50 words] This study aims to analyze the influence of students' learning styles (visual, auditory, and kinesthetic) on their English learning outcomes among fourth-grade students at MIN Bontolangkasa. Methodology: This quantitative correlational research used a learning style questionnaire (30 items) and documentation of English semester test scores. Data from 41 students were analyzed using descriptive statistics and simple linear regression with SPSS Version 22 software. Main Findings: The dominant learning style was visual. However, statistical analysis showed no significant influence of learning styles on English learning outcomes. The average English score was 70.40, and factors such as uniform teaching methods and the local linguistic environment were suspected to moderate the relationship. Novelty/Originality of this study: This study provides empirical evidence from a Madrasah Ibtidaiyah (Islamic elementary school) in a rural Indonesian context, highlighting that learning style theory may not be a primary determinant of achievement when other contextual and pedagogical factors are predominant